MALAPARI (Pongamia Pinnata (L.) Piere) GROWTH ON THREE PLANTING PATTERNS WITH Trichoderma AND Mycorrhizae APPLICATION - Hani, Aditya; Dendang, Benyamin; A. G. Pieter, Levina (Indonesian Journal of Forestry Research, 2021)
Malapari (Pongamia pinnata) is a potential plant for biodiesel and has the ability to grow on marginal land. Malapari cultivation has not yet been carried out due to low economic value. Agroforestry crop patterns are expected to provide intermediate results so that people would be interested in planting malapari. Planting on coastal land requires the right technology to produce optimal growth. This study aims to determine the effect of malapari cropping patterns and evaluate biological fertilizer application in the seedling phase after planting in the field. The research uses a split plot design (Split Plot Design) with the main factors that are the pattern of malapari planting and sub-plots that are the type of application of biofertilizer. The results obtained from the study showed that the interaction of cropping pattern treatment and biofertilizer application did not give significant growth to malapari; the combination of the application of organic manure, Trichoderma spp. and mycorrhiza bio-fertilizers in the nursery yielded the largest malapari diameter growth after planting in the field at the age of 3 years.